International News In Shaping The National Daily Agenda - Kurysheva, Yulia Vladimirivna; Potolokova, Maria Olegovna; Nikonov, Sergey Borisovich; Samsonova, Anastasiia Aleksandrovna; Kovalenko, Boris Nikiforovich (The journal of contemporary issues in business and government, 2021)
The world picture of the national audience is predominantly formed by the following media sources: world mass media; national mass media; selected personal Internet-based sources. Under the Internet-based sources we understand news sources of different types on the Internet-platforms. They can have or don’t have official character, can be or not to be professional ones, may have different degrees of confidence, whether or not to have the characteristics of a professional mass media. The research is based on publications of national newspapers belonging to three different journalistic cultures: the British national version "Guradian", the Russian "Kommersant" and the Spanish "ABC". In the modern world, the frequency of news feed updates does not allow a newspaper to rely only on its own sources of information, so when preparing news texts, national media journalists also rely on the materials of third-party subjects. From this point of view, the analysis includes studying the geographical agenda (the range of countries covered on a regular basis and frequency of mentioning), identifying the types of content, the main sources of information, and their relationship to the range of countries under coverage.